Relationships of lower extremity and trunk asymmetries in elite soccer players - Maly, Tomas; Hank, Mikulas; Verbruggen, Ferdia Fallon; Clarup, Christian; Phillips, Kirk; Zahalka, Frantisek; Mala, Lucia; Ford, Kevin R. (Frontiers in Physiology, 2024)
In light of previous research highlighting the prevalence of asymmetries in soccer players and possible links to injury risks, there is a missing link in biomechanical understanding of complex relationships between lower extremity and trunk asymmetries in elite soccer. Purpose: The purpose of the study was to investigate the level, relationships, and differences between twelve different parameters of strength, morphological, and neuromuscular asymmetries in elite soccer players.Methods: Elite male soccer players (n = 25, age 21.7±3.9 years) were tested in the following tests: bilateral fluid distribution, hip flexor range of motion, postural stability, isokinetic strength of knee extensors and flexors , isometric lateral trunk rotation strength, eccentric strength of knee flexors, isometric bilateral strength of hip adductors and vertical ground reaction force in counter movement jump-free arms, counter movement jump, squat jump, drop jump tests. One-way ANOVA, Pearson's coefficient (r), and Partial eta squared (ηp 2 ) were used within data analysis.Results: Significant differences in asymmetries were found in elite soccer players (F11,299 = 11.01, p<.01). The magnitude of asymmetry over 10 % were in postural stability and drop jump parameters. The lowest magnitudes of asymmetries were in fluid distribution of lower limbs and in the vertical ground reaction force during take-off phase in squat jump. The highest asymmetries between dominant and non-dominant sides were found in postural stability and drop jump. A total of eleven significant correlations (p<0.05, r = 0.41 -63, R2 = 0.17 -0.40) were found between analysed asymmetries in elite soccer players. The lateral trunk rotation asymmetries were significantly correlated to vertical ground reaction force asymmetries and knee extensors. .Long-term exposure in elite soccer leads to unilateral biomechanical loading that induces abnormal strength and morphological adaptations in favor of the dominant side, while linking lower limb and trunk strength asymmetries. By unraveling these complex relationships, we strive to contribute novel methods that could inform targeted training regimes and injury prevention strategies in the elite soccer community. Data should encourage future researchers and coaches to monitor and develop trunk strength linked to lower body kinematics.